Isotherm Adsorption of Ion Phosphate from Vinasse Waste Using Quaternary Ammonium Polymer as Adsorbent in Term Effect of Temperature - Veranica; Rahayu, Aster; Maryudi; Dhias Cahya Hakika; Lee Wah Lim; Lia Anggresani (Sains Natural: Journal of Biology and Chemistry, 2024)
Vinasse liquid waste is a waste product resulting from the ethanol distillation process. Phosphate in high concentrations can harm the environment, such as by polluting water sources and underground surfaces. In this research, adsorption of phosphate ions was carried out in vinasse waste to remove these pollutants using quaternary ammonium polymers. The study examined the effect of vinasse waste sample temperature on the adsorption of phosphate ions. The first step in this work was to create a quaternary ammonium polymer utilising a one-pot technique using 2-[methacryloyloxy)ethyl trimethylammonium chloride solution, also referred to as META. Subsequently, the adsorption process was performed using temperature variations of 25, 30, 40, 50, and 60 . Phosphate ion adsorbance was measured with UV-Vis spectrometers at a wavelength of 880 nm. The quaternary ammonium polymer succeeded in adsorbing the phosphate ion content of the vinasse waste at an optimal temperature of 40 , with an adsorption capacity of 3.78 mg/L and a removal efficiency of 75.70%.  The adsorption isotherm model for phosphate ions onto quaternary ammonium polymer was studied using the Freundlich and Langmuir equations. The obtained data indicated that the Langmuir isotherm model, with an value of 0.9921, is well-suited for describing the adsorption behaviour in this research.